Post-Processing of 3D-Printed Polymers - John Ryan C. Dizon; Ciara Catherine L. Gache; Honelly Mae S. Cascolan; Lina T. Cancino; Rigoberto C. Advincula (Technologies, 2021)
Additive manufacturing, commonly known as 3D printing, is an advancement over traditional formative manufacturing methods. It can increase efficiency in manufacturing operations highlighting advantages such as rapid prototyping, reduction of waste, reduction of manufacturing time and cost, and increased flexibility in a production setting. The additive manufacturing (AM) process consists of five steps: (1) preparation of 3D models for printing (designing the part/object), (2) conversion to STL file, (3) slicing and setting of 3D printing parameters, (4) actual printing, and (5) finishing/post-processing methods. Very often, the 3D printed part is sufficient by itself without further post-printing processing. However, many applications still require some forms of post-processing, especially those for industrial applications. This review focuses on the importance of different finishing/post-processing methods for 3D-printed polymers. Different 3D printing technologies and materials are considered in presenting the authors’ perspective. The advantages and disadvantages of using these methods are also discussed together with the cost and time in doing the post-processing activities. Lastly, this review also includes discussions on the enhancement of properties such as electrical, mechanical, and chemical, and other characteristics such as geometrical precision, durability, surface properties, and aesthetic value with post-printing processing. Future perspectives is also provided towards the end of this review.